PERANCANGAN TRANSFORMASI INSTITUSI PENYELENGGARA DAN PENGELOLA SERTIFIKASI HALAL DI INDONESIA DENGAN PENDEKATAN SOFT SYSTEM METHODOLOGY: STUDI KASUS DI LPPOM MUI - Sumunar Jati; Musa Hubeis; Gendut Suprayitno (Jurnal Aplikasi Bisnis dan Manajemen (JABM), 2021)
Recently, halal industries have shown impressive growth in global and national market levels. The purpose of this research is designing the managing and administering institution of halal certification (LPPOM MUI) in order to maintain its functions and roles in the new era of regulations (UUJPH) and the growing of halal ecosystem in industrial digital era 4.0. Soft System Methodology (SSM) is used as the methodology. SSM is an organization process modeling that can be used to solve unstructure general problem and management changing. Rich Picture, Root Definition, and Conceptual Model are presented in this paper. Data was collected by using Focus Group Discussions, involved in the process and in-depth interviews with the Government, MUI, LPPOM MUI, business player, and the public community of halal. The focus of this research is getting knowledge of people, their behaviours, their relationships and their influence to LPPOM MUI transformation and the development of corporate and operational strategies. Based on the analysis, there are eight main results as a key strategy of institution transformation, as follows :(i)identification of people, (ii) institution form, (iii) vision, mission, culture, and values evaluation, (iv) operational evaluation based on resource-based view, (v) legal entity transformation, (vi) managerial improvement, (vii) measurement of marketing and financial performance, and (viii) risk mitigation. Keywords: business strategy, halal regulation, soft system methodology, transformation